A Comparative Study of Levetiracetam and Phenobarbital for Neonatal Seizures as a First Line Treatment. (December 2022) - Akeel, Nagwa Elsayed; Suliman, Hany Abdelaziz; Al-Shokary, Ashraf Hamed; Ibrahim, Asmaa Obada; Kamal, Naglaa M.; Abdelgalil, Abobakr Abosree; Elmala, Moustafa Kotb; Elshorbagy, Hatem Hamed; Nasef, Khaled Amin; Attia, Ahmed Mahmoud; Fathallah, Mohamed Gamal El Din
Objectives: We aimed to evaluate the use of intravenous levetiracetam as the first-line treatment of neonatal seizures compared with phenobarbital. Methods: The study was conducted on 104 neonates (0-28 days) with clinical seizures after inclusion criteria. They were assigned in equal ratio into 2 groups; 1 included neonates who received phenobarbitone, and the other included neonates who received levetiracetam. Neonates were loaded with 20 mg/kg of intravenous drug-A (phenobarbitone) or drug-B (levetiracetam). In persistent seizures, a second loading dose of the same drug was given. Crossover to other drugs occurred if seizures persisted after the second dose of the same drug. The proportion of neonates who achieved cessation of seizures following the first or second loading dose of either drug-A or drug-B (PB or LEV) was the main outcome measure provided that they remained free of seizure for the following 24 hours. Results: After 1 or 2 doses of Levetiracatam or Phenobarbitone, clinical seizures stopped (and remained seizure-free for 24 hours) in 41 (78.84%) and 34 (65.38%) patients, respectively ( P  = .01). Neonates in the LEV group showed better seizure control than neonates in the PB group (RR = 0.57; 95% CI (0.17, 0.80). We did not report any adverse drug reactions in the LEV group. However, 12 (23.07%) neonates developed adverse drug reactions in the PB Group. Conclusion: Levetiracetam is considered an effective and safe drug as a first-line AED in neonatal seizures.